2021
DOI: 10.1084/jem.20202001
|View full text |Cite
|
Sign up to set email alerts
|

Human marginal zone B cell development from early T2 progenitors

Abstract: B cells emerge from the bone marrow as transitional (TS) B cells that differentiate through T1, T2, and T3 stages to become naive B cells. We have identified a bifurcation of human B cell maturation from the T1 stage forming IgMhi and IgMlo developmental trajectories. IgMhi T2 cells have higher expression of α4β7 integrin and lower expression of IL-4 receptor (IL4R) compared with the IgMlo branch and are selectively recruited into gut-associated lymphoid tissue. IgMhi T2 cells also share transcriptomic feature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 52 publications
2
74
0
Order By: Relevance
“…In some animal species, for example, birds, rabbits, and sheep, GALT play a role in the generation of primary diversity of B cell receptors as random mutations or parts of upstream pseudogenes are introduced into the V regions, but in human and mice they are mainly involved in shaping specific immune responses 79 . However, even in mice and humans, the gut has been suggested to take part in early B cell development, and both VDJ recombination and selection of transitional B cells into specific B cell lineages have been described 80‐83 . Unexpectedly, some recent single‐cell RNASeq studies have also found gene expression patterns suggestive for early B cell development in the meningeal tissues of the CNS, 84,85 with two studies even reporting a brain associated lymphopoietic niche 86,87 .…”
Section: Inductive and Effector Sites For Mucosal Iga Responsesmentioning
confidence: 99%
“…In some animal species, for example, birds, rabbits, and sheep, GALT play a role in the generation of primary diversity of B cell receptors as random mutations or parts of upstream pseudogenes are introduced into the V regions, but in human and mice they are mainly involved in shaping specific immune responses 79 . However, even in mice and humans, the gut has been suggested to take part in early B cell development, and both VDJ recombination and selection of transitional B cells into specific B cell lineages have been described 80‐83 . Unexpectedly, some recent single‐cell RNASeq studies have also found gene expression patterns suggestive for early B cell development in the meningeal tissues of the CNS, 84,85 with two studies even reporting a brain associated lymphopoietic niche 86,87 .…”
Section: Inductive and Effector Sites For Mucosal Iga Responsesmentioning
confidence: 99%
“…Later in the disease course B cell defects may predispose to secondary bacterial infection, which is a major clinical problem in severe COVID (Maes et al, 2021;Ripa et al, 2021). Marginal zone B cells are key players in early defence against blood--borne bacterial infection (Nemazee, 2021) and their dysregulation may play a role in autoimmunity (Tull et al, 2021). MZL B cells are profoundly reduced in COVID--19 in humans, and hypoxia results in MZs almost devoid of B cells in mice.…”
Section: Discussionmentioning
confidence: 99%
“…MZL B cells in humans, and MZ cells in hypoxic mice, also recover more slowly than other B cell subsets. The reasons for this are unknown, but human MZ B cells appear to be derived from T2 transitional B cells and/or memory B cells (Kibler et al, 2021;Tull et al, 2021), both of which are profoundly depleted in COVID--19. This alone may hamper recovery, but additional unknown factors may also determine reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…The elephant at issue, the marginal zone B cell (MZB), does not fall neatly into innate or adaptive compartments but displays elements of both. Here, we highlight two papers on human MZB development and memory (Tull et al, 2021;Kibler et al, 2021), which look at both ends of the beast. By applying single-cell RNA sequencing (RNA-seq), flow spectrometry, and antibody gene mutational analysis techniques, these studies provide a higher-resolution view of these enigmatic compartments.…”
mentioning
confidence: 99%
“…Our first band of intrepid explorers, Tull et al (2021) noted that human T2 cells express α4β7 integrins necessary for migration to the gut-associated lymphoid tissue (GALT), and that this expression is reduced in systemic lupus erythematosus (SLE; Vossenkämper et al, 2013), leading them to study these B cell subsets in normal and lupus patients. Flow spectrometry and single-cell RNA-seq analysis identified two apparent lineages of transitional B cells in the blood differing in cell surface marker and RNA expression.…”
mentioning
confidence: 99%